2014
DOI: 10.1016/j.chemosphere.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic toxicity of six anticancer drugs on rotifers and crustaceans

Abstract: The growing use of cytostatic drugs is gaining relevance as an environmental concern. Environmental and distribution studies are increasing due to the development of accurate analytical methods, whereas ecotoxicological studies are still lacking. The aim of the present study was to investigate the acute and chronic toxicity of six cytostatics (5-fluorouracil, capecitabine, cisplatin, doxorubicin, etoposide, and imatinib) belonging to five classes of Anatomical Therapeutic Classification (ATC) on primary consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(59 citation statements)
references
References 34 publications
2
50
2
5
Order By: Relevance
“…Although in previous studies a comparable toxicological sensitivity was demonstrated for D. magna and C. dubia (Constantine and Huggett 2010;Parrella et al 2014a), the genotoxicity results here reported showed a different effect of binary mixtures in the two cladocerans. It was reported by Hayasaka et al (2012) that body size was correlated with an organism's sensitivity to toxicants.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Although in previous studies a comparable toxicological sensitivity was demonstrated for D. magna and C. dubia (Constantine and Huggett 2010;Parrella et al 2014a), the genotoxicity results here reported showed a different effect of binary mixtures in the two cladocerans. It was reported by Hayasaka et al (2012) that body size was correlated with an organism's sensitivity to toxicants.…”
Section: Resultscontrasting
confidence: 67%
“…Considering their stability, the continuous release of anticancer drugs (Negreira et al 2014) may reduce, as other genotoxic xenobiotics, the viability of aquatic species resulting in an alteration of the ecosystem (Moe et al 2013). Reproductive toxicity and DNA damage are sometimes closely related in aquatic organisms (Jha 2008), and the detection of chronic toxicity as well as genotoxicity in crustaceans exposed to anticancer drugs is of eco-toxicological relevance (Parrella et al 2014a(Parrella et al , 2015. In this context, to better understand the interactions of compounds damaging DNA, with different molecular mechanisms and properties, binary mixtures rather than single compounds were tested to predict their interactions and to provide more information about the complexity of responses of aquatic species to anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In C. dubia, most mixtures had antagonist interactions except for IM + 5-FU and IM + CDDP that showed Bliss independence. This corroborate the findings of a previous reproductive toxicity study with D. magna and C. dubia revealing that the majority of these binary mixtures exerted an independent action (Parrella et al, 2014a). When comparing the effective concentrations of a binary mixture to those of the single compounds (Parrella et al, 2014b), combinations of anticancer drugs could be of environmental concern because their effects occur at very low concentrations that are in the range of concentrations encountered in aquatic systems.…”
supporting
confidence: 88%
“…Moreover, graphene and graphene oxide (GO) exhibit improved performances in removing organic dyes, pharmaceutical antibiotics, and aromatic compounds due to their large specific surface area and/or massive functional groups on their surface151617. GO, which is structurally similar to graphene, possesses a large quantity of oxygen-containing epoxy, hydroxyl, and carboxyl groups, and the presence of these functional groups has rendered GO highly hydrophilic and thus suitable for use in aquatic and biological environments1819.…”
mentioning
confidence: 99%